2016
DOI: 10.1542/peds.2015-2851i
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Behavioral Correlates of Depression History in Children and Adolescents With Autism Spectrum Disorder

Abstract: Background Depression is a common psychiatric problem associated with autism spectrum disorder (ASD) across the lifespan. Objective We sought to identify medical and behavioral problems associated with a history of a parent reported diagnosis of depression in a large sample of school-aged children and adolescents with ASD. Methods A sample of 1272 participants (age 6–17 years, M=9.56, SD=2.79) from the Autism Speaks-Autism Treatment Network (AS-ATN) consortium was divided into “Ever-Depressed” (n=89) and “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 50 publications
6
40
0
2
Order By: Relevance
“…Moving forward, conclusions from our analyses and others [e.g., ( 24 , 25 , 27 )] regarding the links between psychiatric and GI comorbidities among individuals with ASD would be strengthened by use of longitudinal data that could inform questions of causality and the direction of effects between symptoms. Our findings are consistent with interpretations positing a causal influence such that the presence of GI symptoms are associated with increased likelihood of mental health symptoms, either as a result of ongoing physical discomfort and/or as a behavioral expression of that discomfort.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moving forward, conclusions from our analyses and others [e.g., ( 24 , 25 , 27 )] regarding the links between psychiatric and GI comorbidities among individuals with ASD would be strengthened by use of longitudinal data that could inform questions of causality and the direction of effects between symptoms. Our findings are consistent with interpretations positing a causal influence such that the presence of GI symptoms are associated with increased likelihood of mental health symptoms, either as a result of ongoing physical discomfort and/or as a behavioral expression of that discomfort.…”
Section: Discussionmentioning
confidence: 87%
“…As early as preschool age, children with ASD with significant GI symptoms demonstrate higher levels of internalizing, aggressive, and repetitive behavior, with positive correlations between GI and behavioral symptoms ( 24 ). Among older children and adolescents with ASD, increased GI symptoms appear to be associated with general affective problems ( 25 ), as well as with more specific psychiatric symptoms such as anxiety ( 26 ), depression ( 27 ), irritability ( 26 ), and self-injurious behavior ( 28 ). Thus, links between GI and psychiatric concerns span both internalizing and externalizing spectrums.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal (GI) symptoms are four-fold more prevalent in ASD than in the general population, with constipation as the most commonly reported symptom (Aldinger et al, 2015; Doshi-Velez et al, 2014; Greenlee et al, 2016; Kohane et al, 2012; Viscidi et al, 2014). The largest prospective study of GI disorders in ASD found that functional constipation was more common in children who were minimally verbal (Gorrindo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ASD 아동 및 청소년이 적어도 하나 이상의 다른 정신장애를 가질 확률은 약 78.7%로 보고되며 (Mannion, Leader, & Healy, 2013) 이 는 추후 발달에 부정적인 영향을 미치므로 추가적으로 이에 맞는 적절한 치료가 제공되어야 한다 (Leyfer et al, 2006;Mattila et al, 2010 (Stewart, Barnard, Pearson, Hasan, & O'Brien, 2006). 이는 정상발달군에 비해 높은 유병률 (Strang et al, 2012)로 연령이 증가할수록, 기능 수준이 높 을수록 취약한 것으로 나타났다 (Greenlee, Mosley, Shui, Veenstra-VanderWeele, & Gotham, 2016;Mazurek & Kanne, 2010).…”
Section: Asd의 공병률unclassified